The Relationship between Boredom Proneness, Attachment Styles and Compulsive Sexual Behavior. Issue 2 (17th February 2023) - Coleman, Eli; Rahm-Knigge, Ryan L.; Danielson, Samuel; Nielsen, Katja H.; Gleason, Neil; Jennings, Todd; Miner, Michael H.
Abstract: Affect regulation is associated with compulsive sexual behavior (CSB) despite ongoing debate about its inclusion in diagnostic criteria. Previous studies on two specific affect regulation constructs – boredom proneness and attachment styles – suggest that affect regulation is associated with CSB. We tested a moderation model of the effects of attachment anxiety and attachment avoidance on the relationship between boredom proneness and CSB. Results indicate that the relationship between boredom proneness and CSB is stronger at higher levels of attachment anxiety, with no interaction between boredom proneness and attachment avoidance. Overall findings support the importance of affect regulation in conceptualizing and treating CSB.